Targeting Ubiquitin-Proteasome Pathway by Natural Products: Novel Therapeutic Strategy for Treatment of Neurodegenerative Diseases - Momtaz, Saeideh; Memariani, Zahra; El-Senduny, Fardous F.; Sanadgol, Nima; Golab, Fereshteh; Katebi, Majid; Abdolghaffari, Amir Hossein; Farzaei, Mohammad Hosein; Abdollahi, Mohammad (Frontiers in Physiology, 2020)
Misfolded proteins are the main common feature of neurodegenerative diseases, thereby, normal proteostasis is an important mechanism to regulate the neural survival and the central nervous system functionality. The ubiquitin-proteasome system (UPS) is a non-lysosomal proteolytic pathway involved in numerous normal functions of the nervous system, modulation of neurotransmitter release, synaptic plasticity, and recycling of membrane receptors or degradation of damaged and regulatory intracellular proteins. Aberrant accumulation of intracellular ubiquitin-positive inclusions has been implicated to a variety of neurodegenerative disorders such as Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington disease (HD), Amyotrophic Lateral Sclerosis (ALS), and Multiple Myeloma (MM). Genetic mutation in deubiquitinating enzyme could disrupt UPS and results in destructive effects on neuron survival. To date, various agents were characterized with proteasome-inhibitory potential. Proteins of the ubiquitin-proteasome system, and in particular, E3 ubiquitin ligases, may be promising molecular targets for neurodegenerative drug discovery. Phytochemicals, specifically polyphenols (PPs), were reported to act as proteasome-inhibitors or may modulate the proteasome activity. PPs modify the UPS by means of accumulation of ubiquitinated proteins, suppression of neuronal apoptosis, reduction of neurotoxicity, and improvement of synaptic plasticity and transmission. This review attempts to summarize the latest reports on the neuroprotective properties involved in the proper functioning of natural polyphenolic compounds with implication for targeting ubiquitin-proteasome pathway in the neurodegenerative diseases. We highlight the evidence suggesting that polyphenolic compounds have a dose and disorder dependent effects in improving neurological dysfunctions, and so their mechanism of action could stimulate the UPS, induce the protein degradation or inhibit UPS, and reduce protein degradation. Future studies should focus on molecular mechanisms by which PPs can interfere this complex regulatory system at specific stages of the disease development and progression.